A Modified Method for Dextrin-capped Gold Nanoparticle Synthesis - Yrad, Flora M. (Silliman Journal, 2022)
Dextrin methodology is an aqueous alkaline chemical process for gold nanoparticle (AuNP) synthesis that takes eight long hours of reaction. A modified procedure is hereby described to simplify the procedure and equipment, and reduced the reaction time to only one hour. The key features of the modified protocol are the reversal of the addition of reagents in the original dextrin protocol and the increase of reaction temperature. Optimum synthesis was achieved by sequential neutralization of 50 mL of 2 mM HAuCl4 with 0.5 mL of 10% Na2 CO3 and alkaline reduction using selected volumes of 25 g/L dextrin. The AuNPs produced were monodisperse based on dynamic light scattering (DLS) measurements. The surface plasmon resonance band ranged from 517 to 520 nm indicating spherically-shaped AuNPs. High resolution transmission electron microscopy (HRTEM) further confirmed the spherical shape with average sizes from 7.3 ± 1.1 to 18.9 ± 1.5 nm, depending on the volume of dextrin. Chemical reactions are hereby proposed to explain the chemistry of AuNP formation based on the alkaline reduction of [AuCl4 ] - complex with dextrin as the reducing agent.